FROM THE PUBLISHER. Community Health Workers Can Bridge The Gap. - TORBAY, RABIH (Health Affairs, 2024)
The article focuses on the critical role of community health workers in addressing barriers to healthcare access in the United States. These workers serve as essential links between communities, particularly in underserved areas, and the healthcare system, helping to build trust and improve health outcomes. Evidence shows that their interventions can enhance chronic disease management and reduce hospital readmissions. However, the article emphasizes the need for better support, training, and compensation for community health workers to ensure their integration into the healthcare system and to effectively address the growing public health challenges in the U.S.